Strain‐Induced Precipitation Behavior of a Nb–Ti–V Steel in the Austenite Phase Field. Issue 9 (28th February 2013) - Nöhrer, Matthias; Zamberger, Sabine; Leitner, Harald
Abstract The precipitation behavior of a Nb (0.041 wt%), V (0.11 wt%), and Ti (0.018 wt%) micro‐alloyed steel influenced by a deformation process in the austenite region has been investigated by transmission electron microscopy and atom probe. After solution annealing at 1250°C, nearly the entire Nb and V amount is in solid solution. Ti does not go into in solid solution and stays stable as TiN precipitates. During the cooling process to deformation temperature, these TiN precipitates act as nucleation sites for Nb and V. Precipitates with a TiN rich core and a V‐rich shell are formed. Nb is homogenously distributed over the precipitate. After deformation, strain induced precipitates occur, which consist mainly of Nb, V, and only a little Ti. Smaller strain induced precipitates have a higher N‐content than C, with growth the C‐content increases.